Rapid fabrication of functionalised poly(dimethylsiloxane) microwells for cell aggregate formation. (9th March 2017) - Forget, A.; Burzava, A. L. S.; Delalat, B.; Vasilev, K.; Harding, F. J.; Blencowe, A.; Voelcker, N. H.
Abstract : Cell aggregates reproduce many features of the natural architecture of functional tissues, and have therefore become an important in vitro model of tissue function. Abstract : Cell aggregates reproduce many features of the natural architecture of functional tissues, and have therefore become an important in vitro model of tissue function. In this study, we present an efficient and rapid method for the fabrication of site specific functionalised poly(dimethylsiloxane) (PDMS) microwell arrays that promote the formation of insulin-producing beta cell (MIN6) aggregates. Microwells were prepared using an ice templating technique whereby aqueous droplets were frozen on a surface and PDMS was cast on top to form a replica. By employing an aqueous alkali hydroxide solution, we demonstrate exclusive etching and functionalisation of the microwell inner surface, thereby allowing the selective absorption of biological factors within the microwells. Additionally, by manipulating surface wettability of the substrate through plasma polymer coating, the shape and profile of the microwells could be tailored. Microwells coated with antifouling Pluronic 123, bovine serum albumin, collagen type IV or insulin growth factor 2 were employed to investigate the formation and stability of MIN6 aggregates in microwells of different shapes. MIN6 aggregates formed with this technique retained insulin expression. These results demonstrate the potential of this platform for the rapid screening of biological factors influencing the formation and response of insulin-producing cell aggregates without the need for expensive micromachining techniques.